A highly stretchable and conductive composite based on an emulsion-templated silver nanowire aerogel. Issue 4 (2nd January 2020) - Tian, Zhilin; Zhao, Yu; Wang, Shaogang; Zhou, Guodong; Zhao, Ni; Wong, Ching-Ping
Abstract : A stretchable and conductive composite was developed based on an isotropic and hierarchical Ag NW aerogel by an emulsion-template method. Abstract : Stretchable and conductive composites are an important component of flexible electronics. However, it still remains a challenge to achieve high stretchability and high conductivity simultaneously in the composites to ensure high reliability in use. In this work, this issue is addressed by developing an emulsion-template method to fabricate a porous silver nanowire (Ag NW)-based aerogel. The aerogel displays an isotropic and hierarchical microstructure with good uniformity and process controllability. To make the aerogel stretchable, the open cells in the aerogel are infiltrated with an elastomer. The obtained composite exhibits high conductivity (65.7 S cm −1 ) and good stretchability (130% strain) at a remarkably low density (50 mg cm −3 ) of Ag NWs, which is enabled by the formation of a three-dimensional conductive and flexible network. The study suggests that the emulsion-templated Ag NW aerogel could be a good candidate for the conductive scaffold of highly stretchable conductors.